Potential NICU Environmental Influences on the Neonate's Microbiome: A Systematic Review - Hartz, Lacey E; Bradshaw, Wanda; Brandon, Debra H (Advances in neonatal care, 2015)
To identify how the neonatal intensive care unit (NICU) environment potentially influences the microbiome high-risk term and preterm infants. Electronic databases utilized to identify studies published in English included PubMed, Google Scholar, Cumulative Index for Nursing and Allied Health Literature, and BioMedSearcher. Date of publication did not limit inclusion in the review. Two hundred fifty articles were assessed for relevance to the research question through title and abstract review. Further screening resulted in full review of 60 articles. An in-depth review of all 60 articles resulted in 39 articles that met inclusion criteria. Twenty-eight articles were eliminated on the basis of the type of study and subject of interest. Studies were reviewed for information related to environmental factors that influence microbial colonization of the neonatal microbiome. Environment was later defined as the physical environment of the NICU and nursery caregiving activities. Studies were characterized into factors that impacted the infant's microbiome—parental skin, feeding type, environmental surfaces and caregiving equipment, health care provider skin, and antibiotic use. Literature revealed that various aspects of living within the NICU environment do influence the microbiome of infants. Caregivers can implement strategies to prevent environment-associated nosocomial infection in the NICU such as implementing infection control measures, encouraging use of breast milk, and decreasing the empirical use of antibiotics.